Ecological and energy aspects of choice of tail units of sewage waterpurifying schemes at treatment of metal in machine construction technologies - A. P. Nesenchuk; V. M. Kopko; T. V. Ryzhova; N. A. Mandel; R. B. Vais; N. G. Malkevich (Литьë и металлургия)
Saving of natural and energy resources at application of thermal technologies of pickling production sewage purifying schemes during metal treatment in machine construction technologies.